2018
DOI: 10.1093/cid/ciy980
|View full text |Cite
|
Sign up to set email alerts
|

Measles Seroprevalence and Vaccine Responses in Human Immunodeficiency Virus–infected Adolescents and Adults: A Systematic Review

Abstract: Background The World Health Organization (WHO) recommends an additional dose of measles-containing vaccine (MCV) for human immunodeficiency virus (HIV)–infected children receiving highly active antiretroviral therapy following immune reconstitution. We conducted a systematic review to synthesize available evidence regarding measles seroprevalence and measles vaccine immunogenicity, efficacy, and safety in HIV-infected adolescents and adults to provide the evidence base for recommendations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Although the WHO recommendations support the administration of an additional dose of measles-containing vaccines for children with HIV on ART following immune reconstitution, they do not recommend the routine administration of an additional dose of a measles-containing vaccine in adults with HIV. However, the data to support the WHO recommendation in adults with HIV are based on a limited number of studies in both adolescents and adults from varying time periods from around the world that show no difference in seroprevalence rates among adolescents and adults with and without HIV [ 19 ]. Measles serology is not routinely collected in PWH, so knowing which patients are at risk for seronegativity and thus stand to benefit from vaccination could help providers apply the guidelines to their practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the WHO recommendations support the administration of an additional dose of measles-containing vaccines for children with HIV on ART following immune reconstitution, they do not recommend the routine administration of an additional dose of a measles-containing vaccine in adults with HIV. However, the data to support the WHO recommendation in adults with HIV are based on a limited number of studies in both adolescents and adults from varying time periods from around the world that show no difference in seroprevalence rates among adolescents and adults with and without HIV [ 19 ]. Measles serology is not routinely collected in PWH, so knowing which patients are at risk for seronegativity and thus stand to benefit from vaccination could help providers apply the guidelines to their practices.…”
Section: Discussionmentioning
confidence: 99%
“…Response to measles vaccination is not completely known in PWH, as outlined by Loevinsohn et al In 6 studies comprised of 109 measles-seronegative patients, measles immunogenicity postvaccination ranged from 0% to 56%. The studies were dated from 1993 to 2016, with a trend toward higher immunogenicity rates in studies conducted after the introduction of combination ART [ 19 ]. Additionally, Fieberkohn and colleagues found that a third dose of MMR vaccine did not result in a significant improvement in seroprevalence in an HIV-negative population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the three cities, however, we found no significant differences for MMR or Tdap vaccination. As these vaccines are typically associated with childhood receipt or for infant cocooning purposes, it is not surprising that the adults in our sample recalled having received MMR or did not identify with having any pertussis risk given their adult circumstances [48,[53][54][55].…”
Section: Discussionmentioning
confidence: 98%
“…Unlike infection with WT MeV, protective immunity induced by the live attenuated MeV vaccine may not be life-long and waning immunity with secondary vaccine failure can occur (25)(26)(27)(28). Understanding the mechanisms involved in the generation and maintenance of life-long protective immunity to measles is thus critical for assessing the challenges of achieving and sustaining measles elimination through vaccination (29). To that end, we have characterized the cell type-specific sites of viral RNA persistence and evolution of the MeV-specific antibody response in rhesus macaques over 6 months after WT MeV infection.…”
mentioning
confidence: 99%